GCT-02. Imaging response assessment for Central Nervous System Germ Cell Tumours: consensus recommendations from the European Society for Paediatric Oncology Brain Tumour Group (SIOPE-BTG) and North American Children's Oncology Group (COG). (3rd June 2022) - Morana, Giovanni; Shaw, Dennis; MacDonald, Shannon; Alapetite, Claire; Ajithkumar, Thankamma; Bhatia, Aashim; Brisse, Hervé; Jaimes, Camilo; Czech, Thomas; Dhall, Girish; Fangusaro, Jason; Faure-Conter, Cecile; et al.
Abstract: BACKGROUND: Central nervous system (CNS) germ cell tumours (GCT) comprise a heterogeneous and relatively rare group of neoplasms. Improving the ability to conduct international clinical trials for CNS GCT requires use of homogeneous, common objective disease assessments and standardised response criteria. Currently, different criteria are employed between European and North American protocols for assessing radiological disease response. METHODS: An international working group of the European Society for Paediatric Oncology (SIOPE) Brain Tumour Group (BTG) and North American Children's Oncology Group (COG) was therefore established to develop consensus recommendations for imaging response assessment for CNS GCT. The working group first reviewed existing literature and current practices and identified major challenges regarding imaging assessment. RESULTS: New clinical imaging standards were defined for the most common sites of intracranial GCT disease (suprasellar/pineal/bifocal), as well as for definition of loco-regional extension. In particular, clear standards were highlighted for definition of partial response (PR) and complete response (CR) to induction chemotherapy at different sites. Furthermore, growing teratoma syndrome (GTS) was clearly defined [apparent radiological increase in non-germinomatous GCT (NGGCT) size during induction chemotherapy despite normalising/normalised AFP/HCG markers – requiring surgery], to avoid such potential cases being classified as progressive disease (PD). CONCLUSION: This consensus will allow more consistent prospective neuroradiological evaluation of response to therapy for patients with CNS GCT and facilitate direct comparison of treatment outcomes across international studies. Ultimately, it may allow international trials to be developed and undertaken across a larger group of collaborating nations, which will be essential to answer many of the remaining questions for this rare but diverse group of tumours.